Conceptual content and unattended visual features (2009)
McDowell (1994) proposed a philosophical theory about perceptual content −call it “conceptualism”− that states that in every case the content of a visual experience necessarily involves concepts that fully specify every single feature consciously and simultaneously available during the experience. In this paper I will question conceptualism, arguing that some visual experiences carry information about so many objects, properties and relations at the same time that it is unlikely for subjects to possess and implement concepts for every feature represented simultaneously by the experience at that time. If this is the case, then McDowell’s conceptualism is insufficiently grounded.